Development of integration mode proton imaging with a single CMOS detector for a small animal irradiation platform - Schnürle, Katrin; Bortfeldt, Jonathan; Englbrecht, Franz Siegfried; Gianoli, Chiara; Hartmann, Jens; Hofverberg, Petter; Meyer, Sebastian; Niepel, Katharina; Yohannes, Indra; Vidal, Marie; Landry, Guillaume; Hérault, Joël; et al. (Frontiers in Physics, 2023)
A novel irradiation platform for pre-clinical proton therapy studies foresees proton imaging for accurate set-up and treatment planning. Imaging at modern synchrocyclotron-based proton therapy centres with high instantaneous particle flux is possible with an integration mode setup. The aim of this work is to determine an object’s water-equivalent thickness (WET) with a commercially available large-area CMOS sensor. Image contrast is achieved by recording the proton energy deposition in the detector pixels for several incoming beam energies (here called probing energies) and applying a signal decomposition method that retrieves the WET. A single planar 114 mm x 65 mm CMOS sensor (49.5 µm pixel pitch) was used for this study aimed at small animal imaging. In experimental campaigns at two isochronous cyclotron-based facilities, probing energies suitable for small-animal sized objects were produced once with the built-in energy layer switching and the other time using a custom degrader wheel. To assess WET accuracy, a micro-CT calibration phantom with 10 inserts of tissue-mimicking materials was imaged at three phantom-to-detector distances: 3 mm, 13 mm and 33 mm. For 3 mm and 13 mm phantom-to-detector distance, the average WET error compared to the ground truth was about 1% and the spatial resolution was 0.16 ± 0.03 mm and 0.47 ± 0.02 mm, respectively. For the largest separation distance of 33 mm air gap, proton scattering had considerable impact and the WET relative error increased to 30% and the spatial resolution was larger than 1.75 mm. We conclude that a pixelated CMOS detector with dedicated post-processing methods can enable fast proton radiographic imaging in a simple and compact setup for small-animal-sized objects with high WET accuracy and spatial resolution for reasonable phantom-to-detector distances.